Blowholes in continuous cast blooms - Pihura, Defviš (Kovine zlitine tehnologije, 1999)
Industrial experience on the presence of blowholes in continuous cast blooms are summarized. From statistical observations the effect of processing parameters, such as heat resisting lining, oxygen blowing, tapping temperature and chemical composition, especially of silicon and gasses hydrogen, nytrogen, oxygen as well as the formation of carbon monoxyde is deduced.
Keywords: jeklo; kontinuirno litje; mehurčki; procesiranje